PENGARUH STRATEGI EVERYONE IS A TEACHER HERE DALAM PEMBELAJARAN MENULIS LAPORAN PERJALANAN DENGAN BAHASA YANG BAIK DAN BENAR - Wandiyo Wandiyo (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to find out the strategic influence of everyone is a teacher here in learning to write travel reports with good and correct language in class VIII students of Banding Agung 2 Middle School. The research method used in this study is the experimental method. The study population of all eighth grade students of State High School 2 Banding Agung totaled 284 students and research samples in class VIII.3 as an experimental class amounted to 30 students and class VIII.4 as a control class totaling 31 students. Data collection techniques used are test techniques and observation techniques. The data analysis technique used in this study used the data normality test, homogeneity test and t-test with a significant level (α = 0.05). Based on the results of the discussion, the results of the t-test can be proved that H0 is rejected and Ha is accepted by looking at tcount abel ttable which is 5.26 ≥ 1.98 which means that there is a significant influence on the strategy of everyone is a class VIII of SMP Negeri 2 Supreme Appeal in learning to write travel reports in good and correct language.